The empirical analysis on dynamics of currency devaluation, external debt to GDP ratio, and output growth: evidence from Ethiopia - Tesfahun Ayanaw; Samuel Godadaw; Yigermal Maru; Mesele Belay; Tilahun Getnet (Cogent Social Sciences)
This paper aimed to examine the empirical analysis of currency devaluation, external debt to GDP growth rate and output growth dynamics in Ethiopia. To achieve this objective, time series data covering from 1991 to 2022 was used and it was examined using an Auto Regressive Distributed Lag (ARDL) model. The estimation results show that devaluation, the external debt-to-GDP growth rate, and economic growth are all significantly correlated and are co-integrated in the long run. This study found that devaluation has positive long-run effect on output growth, while the external debt-to-GDP growth rate has negative long-run effects on output growth. In addition, the results revealed that inflation had positive effects on economic growth both in the short and long run, while, private investment had negative effects on economic growth both in the short and long run respectively. In general, the study found that there is no short-run connection between devaluation, the external debt-to-GDP growth rate, and economic growth; nevertheless, in the long run, devaluation lowers external debt by boosting exports and promoting economic growth. Additionally, long-run economic growth in the country is positively impacted by spending on education and the availability of real money supply. This study suggests that the government should improve economic growth by enhancing allocation for education to improve its quality, control inflation and money supply, and promoting devaluation to check their effects on the economy.